A novel cross-institutional college internship program to train future diverse leaders in clinical research with data-driven approaches to assess impact - Julia Derk; Julia Derk; Julia Derk; Kafui Dzirasa; Kafui Dzirasa; Kafui Dzirasa; Kafui Dzirasa; Tracie Locklear; Tracie Locklear (Frontiers Media S.A., 2023)
The field of Clinical Research, like many other scientific disciplines, has struggled to recruit and retain talented researchers from diverse communities. While there is a strong history of documenting the problem, having a diverse and inclusive workforce is hindered by the lack of data-driven approaches, cross-institutional partnerships, access to mentors, and positive immersive experiences for people from underrepresented groups. Here, we describe a novel initiative for North Carolina Central University Clinical Research Sciences Program (NCCU-CRSP) student interns to partner with Duke University to have immersive clinical and pre-clinical research training in a 15-week internship as the culminating experience towards their degree for a Bachelor of Science in Clinical Research. The goals of the internship are: 1) to give hands-on training to enhance the impact of classroom-based learning, 2) broaden their understanding of the wide swath of positions available to them, 3) promote their sense of self-efficacy, confidence, science identity, research identity, and connections to the pre-clinical and clinical community, and 4) prepare them to be workforce ready upon graduating. The students dedicate 75% of their time to clinical research with Duke University at Pickett Road and 25% to pre-clinical research in the Collective for Psychiatric Neuroengineering in the Duke Psychiatry Department of the School of Medicine. They will also receive eight 1-h professional development training sessions from the Duke-NCCU Clinical and Translational Science Initiative's Workforce Development Team and five 1-h sessions based on the Entering Research Curriculum developed by the Center for the Improvement of Mentored Experiences in Research (CIMER). Finally, they will be brought in as a cohort and coached on peer mentoring and mutual support frameworks to enhance their sense of community. These student-interns will perform pre- and post-internship self-assessment surveys to quantify their self-efficacy, feelings of belonging, access to research opportunities and mentors, and to give details of their future education and career goals. We will evaluate the impact of the internship using validated tools and apply these findings for future optimization of program design and tactical advice for other programs with shared missions. Furthermore, we will email them on an annual basis with follow-up surveys to assess the longitudinal impact of this internship program, their educational experiences at NCCU, what job titles they hold, how prepared they feel for their roles, and what they hope their future career trajectory will be. Collectively, these approaches will apply theoretical frameworks developed by social and cognitive psychology, vocational theory, and educational research to clinical research training with the goals of recruiting and training talented and diverse leaders within clinical research. We hope that by evaluating our successes, failures, strengths, and liabilities through empirically derived evidence we will also inspire future studies that use data-driven approaches to elevate our approaches as we work together to train and recruit talented researchers from diverse communities into our scientific enterprise and to launch them with more in-depth experiential learning that will empower them to succeed.